Judaism and World Religion - Solomon, Norman. author. aut Link
XVI, 295 p.
Keywords: A text which draws on traditional sources, mainly but not exclusively Jewish, to address contemporary issues, ranging from conservation of the environment, through to business and commercial ethics, to relations between State and religion.